A survey of the birds of Nias Island, Sumatra - Dymond, Nick (KUKILA, 1994)
Details are given of a 17-day visit to Nias, off the west coast of mainland Sumatra. The author travelled around the island searching, in vain, for primary forest and assessing the bird' communities of secondary forest and other habitats. Of twelve species recorded for the first time on the island, three (Treron capellei, Nectarinia jugularis and Passer montanus) are usually regarded as residents. It is postulated that the pigeons were possibly wandering birds from too; mainland, that the sunbirds have been overlooked in the past, and that the sparrows are recent colonists. The continuing status of some 36 previously-recorded resident species, 23 usually associated with forest, that were not seen in 1990 is discussed. Of 25 endemic subspecies, 8 were not seen in 1990 and the survival of 3 of these is considered very doubtful.